My life as a fake - Carey, Peter ([Sydney] : Vision Australia Information and Library Service, 2004)
Sarah Wode-Douglass, editor of a London poetry magazine, had grown up knowing the famous and infamous John Slater. And because he figured prominently in the disaster that was her parents' marriage, when Slater proposes that she accompany him to Malaysia, Sarah embarks on a journey that becomes, instead, a lifelong obsession. Her discoveries spiral outward from Christopher Chubb, a destitute Australian she meets by chance in the Kuala Lumpur. He is mad, Slater warns her, explaining the ruinous hoax Chubb had committed decades earlier. But lurking behind the man's peculiarity, Sarah senses, is artistic genius, in the form of a manuscript he teases her with and which she would do anything to acquire. The provenance of this work, she learns, is marked by kidnapping, exile, and death - and that more than once compels her back to Malaysia without ever disclosing all of its secrets, only the power of the imagination and the prices it can exact from those who would wield it.
Produced under Part VB of the Copyright Act 1968.
This book is part of the Joan Ledermann Memorial Braille Collection.
Shortlisted for the Miles Franklin Award 2004.
For adults.
VAILS (Mel)
Keywords: Literary forgeries and mystifications -- Fiction; British -- Australia -- Fiction; British -- Malaysia -- Fiction; Women editors -- Fiction; Poets -- Fiction; Australian